MRAC Adaptive Control Design for an F15 Aircraft Pitch Angular Motion Using Dynamics Inversion and Fractional-Order Filtering - Amani R. Ynineb; Samir Ladaci (International Journal of Robotics and Control Systems, 2022)
This study proposes a fractional adaptive control scheme design for a longitudinal pitch angular motion control of a military F15 aircraft. The aircraft behavior will be forced to follow a chosen model reference in an MRAC (Model Reference Adaptive Control) configuration combined with dynamics inversion technique such that the transient response becomes invariant even in the presence of uncertainties or variations for a reference input by introducing a fractional-order transfer function pre-filter. Based on Lyapunov theory, the updating control law minimizes the error between the plant output and the model reference one. This controller is set in a cascade with a linear dynamic compensator. Simulation results on a military aircraft model with comparison to preceding results illustrate the effectiveness and the superiority of the proposed control strategy.